Developmentally regulated, low abundance Tec element transcripts in Euplotes crassus--implications for DNA elimination and transposition. - Jaraczewski, J W (1994)
During macromolecular development in the ciliated protozoan, Euplotes crassus, > 105 Tec elements are precisely eliminated from the genome in a 2-4 h time interval, generating extrachromosomal circular forms of the elements. Various models have proposed a transposition-based mechanism for this excision. We have tested this hypothesis by determining the abundance of transcripts of Tec element open reading frames (ORFs) and the timing of their appearance. Transcripts are very low in abundance and are only detected by PCR amplification techniques. Thus, the low levels of transcripts argue against the participation of element-encoded functions in the Tec element elimination process. The element transcripts are only detected in RNA samples from mated cells, indicating that the micronucleus and/or developing macronucleus are transcriptionally active during the sexual phase of the life cycle. The transcription detected could allow a low level of germline-specific transposition for these elements.